Makanan Halal dan Tayyib dalam Perspektif Al-Quran - Sri Mulyati; Achmad Abubakar; Hasyim Hadade (CV Putra Publisher, 2023)
With the increasing trend of demand for halal food, various food products have emerged with many variations to compete in the market, to meet the practical needs of consumers and not to forget the delicacy in food. This is the background for producers in developing their products, so it is not uncommon for some producers to feel the need to add dyes to attract consumers' attention, preservatives, flavorings and even artificial sweeteners, all of which come from chemicals which are considered quite cheap and easy to obtain on the market. Seeing this phenomenon, with the emergence of many